A valorização da natureza na perspectiva da sociedade de consumidores: na utopia para além das redações constitucionais latimo-americanas - Baldissera, Rafaela (2018)
This dissertation proposes a legal reflection on the valorization of Nature, analyzing the effectiveness of the precepts established by the New Latin American Constitutionalism, from the perspective of the current liquid-modern society. Then, using the deductive method, in a theoretical contextualization based on techniques of Bibliographic Research, Category and Operational Concept, it is intended to demonstrate the need for alternatives to overcoming the predominantly consumerist culture, which leads to domination and exploitation of the natural world . Focusing on the Research Line Constitutional Jurisdiction and Democracy, the research seeks to find ways to change the human mind, which remains focused on the superi ority of man in relation to the other elements that integrate the ecosystem. In this line of thought, it is concluded that the Consumer Society will value nature, based on the ideals of the New Latin American Constitutionalism, when it changes the contemporary thinking of everything to dominate and consume.